2022
DOI: 10.1039/d1mh01720a
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of supercritical fluid technology for advancing decellularization and postprocessing of viable biological materials

Abstract: This review summarizes relevant literature on scCO2-assisted decellularization, and discusses major topics dominating the field, such as mechanism of action, effect of cosolvent and operational parameters, and range of results across different works.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 194 publications
(367 reference statements)
0
8
0
Order By: Relevance
“…dsDNA values were higher than the arbitrarily definition of decellularization of 50 ng dsDNA/mg dry scaffold for all scCO 2 methods. Changes in the duration of the decellularization process and addition of co-solvents might help to reduce DNA content in scCO 2 processed scaffolds even more [22] . Previous studies indicated that complete removal of chondrocytes might be undesirable: immunogenicity is low and the recellularization process afterwards is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…dsDNA values were higher than the arbitrarily definition of decellularization of 50 ng dsDNA/mg dry scaffold for all scCO 2 methods. Changes in the duration of the decellularization process and addition of co-solvents might help to reduce DNA content in scCO 2 processed scaffolds even more [22] . Previous studies indicated that complete removal of chondrocytes might be undesirable: immunogenicity is low and the recellularization process afterwards is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…While it is unclear which exact mechanisms occur for collagen in bone, it appears that the increasing SCF‐ethanol treatment time may control whether the ethanol impact on bone's material property is reversible or not after rehydration. Finally, despite ethanol as additive in the SCF‐treatment process significantly improving the fracture toughness, it is important to note that its efficacy as a sterilant additive to achieve the required SAL of 10 −6 is lower than additives such as peracetic acid or hydrogen peroxide 93‐96 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, despite ethanol as additive in the SCF-treatment process significantly improving the fracture toughness, it is important to note that its efficacy as a sterilant additive to achieve the required SAL of 10 À6 is lower than additives such as peracetic acid or hydrogen peroxide. [93][94][95][96]…”
Section: Nalla Et Al Have Shown That Initiation and Growth Toughness ...mentioning
confidence: 99%
“…Other co-solvents have been posed as potential alternatives to enhance scCO 2 efficiency [37]. One such is Dehypon ® , a compound with a molecular weight higher than ethanol that could therefore act as a stronger enhancer of the SCF's density [38].…”
Section: Discussionmentioning
confidence: 99%